Ovarian transcriptome analyses indicate that weak juvenile hormone signaling underlies the molecular basis of oogenesis deficiencies in mosquitoes - Wiśniewska, Monika M; Kolísko, Martin; Berková, Petra; Moos, Martin; Maaroufi, Houda O; Noriega, Fernando G; Nouzova, Marcela (BMC biology, 2025)
BACKGROUND: Juvenile hormone (JH) is synthesized by the corpora allata (CA) and controls development and reproduction in insects. We recently used CRISPR/Cas9 to establish a line lacking the enzyme that catalyzes the final step of JH biosynthesis in mosquitoes, a P450 epoxidase. The CA of the epox-/- mutants do not synthesize epoxidized JH III but methyl farneosate (MF), a weak agonist of the JH receptor. Female epox-/- mosquitoes have reduced JH signaling and show a substantial loss of reproductive fitness. To understand the molecular basis of this loss of fitness, we constructed ovarian mRNA libraries of Ae. aegypti of the Orlando strain wild-type (WT) and epoxidase null mutants (epox-/-) and investigated differential expression of reproductive genes. RESULTS: We performed triplicate RNA-seq analyses of female WT and epox-/- ovaries dissected at four critical stages of oogenesis: Ovaries from newly eclosed females (0h), sugar-fed females at 4 days post-eclosion (4d SF), females 16h (16h BF), and 48 h after a blood meal (48h BF). Silencing of epoxidase resulted in a drastic change in the expression of thousands of genes. CONCLUSIONS: Our results suggest that epoxidase deficiency leads to a reduction in JH signaling that has significant effects on Ae. aegypti ovarian transcriptome profiles. Ecdysteroid titers are dysregulated in the mutants, leading to a significant delay in the expression of vitelline membrane genes and other transcripts. We discovered changes in the expression of 230 long non-coding RNAs (lncRNAs) that may play an important role in the regulation of ovarian genes.
Keywords: signální transdukce; Ecdysteroids; Gene Expression Profiling; transkriptom; Signal Transduction; Aedes; Transcriptome; Ovaries; ženské pohlaví; zvířata; Juvenile Hormones; oogeneze; lncRNA; ovarium; Ovary; Oogenesis; stanovení celkové genové exprese; juvenilní hormony; Aedes aegypti; Female; Juvenile hormone; Animals